419 What are the priorities for older adults attending the ED? Findings from a multiple stakeholder group consensus meeting. Issue 12 (23rd November 2020) - Graham, Blair; Endacott, Ruth; Smith, Jason E; Barham, Ffion; Latour, Jos M
Abstract : Aims/Objectives/Background: Patient Reported Experience & Outcome Measures (PREMs/PROMs) are not yet well established in emergency care. This study aimed to determine priorities for older adults attending the ED, to inform item inclusion for a new PREM/PROM. Methods/Design: One hundred thirty-five priority statements, linked to suggested PREM/PROM items, were derived from the literature, patient interviews (n=24) and staff focus groups (n=7)(October 2018- April 2019). All statements had a Flesch-Kincaid Reading Ease score >70. A one-day consensus meeting was held, December 2019. Invitations were issued via social media, patient/public involvement groups and charities. Following focus groups to assess interpretability, nominal group technique was used to prioritise statements. Individuals scored statements from 1(least important) to 9(most important). Statements with a median score of > 6.5 were 'critically important', 3.5 to 6 'important, not critical', and < 3 'less important'. Inter-rater agreement was assessed using mean absolute deviation from the median (MADM). 'Critically important' or 'less important' statements with MADM <50% were automatically included or excluded, respectively. Statements deemed 'important, not critical', or with MADM >50% underwent further voting. Remaining statements underwent dichotomous voting. A > 70% favourable majority was required for inclusion. Results/Conclusions: Twenty-nine participants attended. Average age was 65.6 years (R32—78). Experiences of emergency care were as a patient (n=16(55.2%)), accompanying person (n=11(37.9%)), third-sector representative (n=14(48.2%)) and/or clinician (n=7(27.6%)). Initial prioritisation yielded 71 statements for inclusion. Further voting led to the inclusion of another 31 statements (102 total). Statements relating to care delivery, communication and emotional needs ranked as more important overall. Statements related to waiting were considered less important ( see supplementary file). Participants reported having 'adequate say' during the meeting (76.9% Strongly Agree). Conclusion: This meeting established priorities for older adults attending the ED. The low priority assigned to waiting confounds some previous findings. Further item reduction is planned to create a final PREM/PROM for older adults.